(untitled) (REMUNOM, 2026)
Population aging is a growing phenomenon worldwide, driven by advances in medicine and increased life expectancy. Despite improvements in health conditions, domestic violence against older people is a serious social and public health problem. This study aimed to understand the impact of domestic violence on the lives of older people and the intervention strategies used by professionals in the protection network. This is an integrative literature review, conducted between 2020 and 2025, in the Scopus, PubMed, SciELO, LILACS, Medline, and BDENF databases. 497 articles were identified; after applying inclusion and exclusion criteria, 19 studies were selected for the final sample. The analysis followed five methodological steps, including problem identification, search, evaluation, analysis, and synthesis of results. Two categories emerged: domestic violence, prevalence, and impact on the lives of older people; and perception and intervention strategies of professionals in the protection network in the face of domestic violence against older people. Studies have shown that violence against elderly people is multifactorial and frequently perpetrated by family members, manifesting itself in physical, psychological, financial, and neglectful forms. Its consequences include emotional suffering, physical illness, and reduced quality of life. In the professional sphere, weaknesses in the protection network were identified, such as a lack of clear care pathways, poor intersectoral coordination, insufficient continuing education, and difficulty in monitoring cases. Primary Health Care emerges as a strategic space for early identification and referral. Overall, the findings reinforce the need to strengthen public policies, improve notification systems, and promote intersectoral interventions. Addressing domestic violence against older people requires a comprehensive approach involving family, community, and the protection network, ensuring safety, care, and dignity.